2006
DOI: 10.1007/s00520-006-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Anastrozole is cost-effective vs tamoxifen as initial adjuvant therapy in early breast cancer: Canadian perspectives on the ATAC completed-treatment analysis

Abstract: Compared to tamoxifen, anastrozole therapy is effective and cost-effective as initial adjuvant therapy in post-menopausal, HR+ early breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 38 publications
2
27
0
2
Order By: Relevance
“…Therapy with ai has already been subjected to numerous cost-effectiveness analyses from the Canadian perspective [11][12][13][14] . However, many of the analyses used assumptions that the matured clinical data do not support, including the assumption that differences in disease-free survival will translate into improvements in overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…Therapy with ai has already been subjected to numerous cost-effectiveness analyses from the Canadian perspective [11][12][13][14] . However, many of the analyses used assumptions that the matured clinical data do not support, including the assumption that differences in disease-free survival will translate into improvements in overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…A second analysis conducted in the United States, on behalf of the ATAC Trialists' Group, concluded that upfront anastrozole is a cost-effective alternative to tamoxifen for the adjuvant treatment of postmenopausal women with estrogen-receptor-positive, early breast cancer 32 . Rochhi and Verma conducted an economic analysis comparing anastrozole and tamoxifen in the adjuvant treatment of hormone-receptor-positive, postmenopausal patients with early breast cancer, using the typical patient from the ATAC trial over a lifetime horizon and the Canadian public healthcare perspective 33 . In that study, resource utilization was drawn from Statistics Canada, supplemented by an expert panel.…”
Section: Discussionmentioning
confidence: 99%
“…"Routine care" included physician visits; blood work; thyroid-stimulating hormone, triiodothyronine, amylase, and lipase tests; and computed tomography and bone scans. Costs of disease progression and death were derived from a previously published study of the cost-effectiveness of breast cancer treatment 42 , assuming that such costs would be independent of cancer type.…”
Section: Costsmentioning
confidence: 99%